If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5d + 5) + -1(d + 1) = 0 Reorder the terms: (5 + 5d) + -1(d + 1) = 0 Remove parenthesis around (5 + 5d) 5 + 5d + -1(d + 1) = 0 Reorder the terms: 5 + 5d + -1(1 + d) = 0 5 + 5d + (1 * -1 + d * -1) = 0 5 + 5d + (-1 + -1d) = 0 Reorder the terms: 5 + -1 + 5d + -1d = 0 Combine like terms: 5 + -1 = 4 4 + 5d + -1d = 0 Combine like terms: 5d + -1d = 4d 4 + 4d = 0 Solving 4 + 4d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4d = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 4d = 0 + -4 4d = 0 + -4 Combine like terms: 0 + -4 = -4 4d = -4 Divide each side by '4'. d = -1 Simplifying d = -1
| -4g=8.2 | | -5x+8+9x=-3(x-1)+5 | | 18+8b=50 | | -(2x+3y)= | | 18=3(6-2x) | | -8x+38=0 | | -8+38=0 | | 7*10+3*30= | | 6+r/3=-2 | | 5(3q-10)-5q=25 | | (-4/5)-(7/8) | | 18+[-(13)]= | | 4y^3u^5*4y*3u^9= | | n+20=-40 | | 12x^3+30x^2-42x= | | 10(m+3)=9m-5(6+m) | | 6/5+2/5x=23/10+3/2x+1/2 | | 18+(-(13))= | | X-3=-3x+5 | | (7x+4)+(x-5)-(2x+5)= | | -5(y-2)-1=10 | | ((52+16)+(52*12))/6 | | -4=6+4p | | 6(4x+8)=288 | | -45=x-12 | | 55-[(25*3)-25]= | | ((52+16)-(52*12))/6 | | 28=2m-2 | | 10m-(2n)= | | (279/3)+((5/6+1/6)+(12-6))*(60+4(25-5))/200 | | 1/2(10x+4)=5x-15 | | 8(x+2)=2/3(12x+24) |